2017
DOI: 10.1111/infa.12187
|View full text |Cite
|
Sign up to set email alerts
|

Coregulation and the Quality of the Relationship in Full‐Term and Very Low‐Birthweight Preterm Infant‐Mother Dyads During Face‐To‐Face Interactions

Abstract: Interactions with parents build the foundation for infants' social-emotional development. This study investigated coregulation of the interaction and quality of relationship between mothers and their 6-month-old full-term (n = 43) and very low-birthweight/preterm (VLBW/preterm; n = 44; ages corrected for prematurity) infants. The objectives were to examine (1) how coregulation changed following a perturbed interaction, (2) how coregulation differed between full-term and VLBW/preterm infant-mother dyads, and (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 60 publications
1
8
0
1
Order By: Relevance
“…Our results indicate that low child EA, reflected in responsiveness and involvement of their mothers may be a risk factor for VLBW/PT children. Our findings are consistent with those of others that indicate that VLBW/PT children have difficulties in socio-emotional domains relative to their fullterm peers (e.g., Doiron and Stack, 2017; Zmyj et al, 2017; Nadeau et al, 2018). They have been demonstrated to have more limited regulatory skills (e.g., Jean and Stack, 2012; Yaari et al, 2018), show more distancing and social monitoring (Montirosso et al, 2010), and rely more on their mothers in a reunion period following the still-face (Jean and Stack, 2012).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results indicate that low child EA, reflected in responsiveness and involvement of their mothers may be a risk factor for VLBW/PT children. Our findings are consistent with those of others that indicate that VLBW/PT children have difficulties in socio-emotional domains relative to their fullterm peers (e.g., Doiron and Stack, 2017; Zmyj et al, 2017; Nadeau et al, 2018). They have been demonstrated to have more limited regulatory skills (e.g., Jean and Stack, 2012; Yaari et al, 2018), show more distancing and social monitoring (Montirosso et al, 2010), and rely more on their mothers in a reunion period following the still-face (Jean and Stack, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…During social interactions, VLBW/PT infants are known to be less alert, more excitable, harder to soothe, and have poorer self-regulation (Jean and Stack, 2012; Provenzi et al, 2017) compared to fullterm infants. Thus, they are poor social partners, and often demonstrate fewer relationship building behaviors, including co-regulation (Doiron and Stack, 2017), making it potentially more difficult for mothers to engage with their infants optimally. Yet, the mother (and father) can be integral in mediating and fostering their social development (e.g., Montagna and Nosarti, 2016; Zmyj et al, 2017) through the frequent interactions that take place as their relationship develops.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it is important to consider that current methodologies that emphasize the initiator and recipient of a tactile contact are a good starting point; however, incorporating more dynamic models where the interaction is considered communicative and bidirectional could provide more complex descriptions of the interaction. For example, a dynamic model approach might help determine the roles the initiator and recipient play in a communicative exchange based on their relationship history over time (for examples of more dynamic methodologies applied to humans, see Doiron & Stack, 2017;Mantis, Stack, Ng, Serbin, & Schwartzman, 2014).…”
Section: Similarities and Differences In Data Collection And Analysesmentioning
confidence: 99%
“…Maternal sensitivity was selected given that research has isolated sensitivity as an important component of maternal emotional availability that affects dyadic behavior (Kaye & Fogel, 1980;Little & Carter, 2005). Previous research has suggested that infants who are less responsive may have more difficulty expressing themselves and, thus, appear unengaged during interactions with their caregivers (Doiron & Stack, 2017). As such, infant responsiveness was also a predictor in order to better investigate its relationship with the various functions of mutual touch.…”
Section: Measures and Observational Codingmentioning
confidence: 99%
“…Investigations of interaction patterns have documented differences in the communicative styles between preterm infant-mother dyads and full-term infant-mother dyads during the first year of life (Doiron & Stack, 2017;Jean & Stack, 2012;White-Traut et al, 2013). From an early age, preterm infants present as more challenging and qualitatively different social partners than full-term infants.…”
mentioning
confidence: 99%